A study on acamecian's turnover intention in higher learning institution - Lim, Geok May. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Employee is the asset for an organization to move forward. It is seen as the “blood” for an organization in order to success. Employees fall under two categories, which are satisfied employees and unsatisfied employees. Satisfied employees generally tend to be more productive as compared to the unsatisfied employees (Oshabemi, 20002; Hom and Gritteth, 1995). Therefore, satisfaction of the academicians is crucial because it is the determinant of the actual turnover for an organization. Factors which contribute to the employees job satisfaction would be determine as it would affect the intention to turnover in an organization. Through this study, it is found that most of the respondents do not have intention to leave their current organization. Factor such as pay, satisfaction on working environment, and people-oriented leadership style has weak negative association towards turnover intention among academicians in higher learning institution. However, opportunities for personal growth and recognition are not significantly affect turnover intention. Last but not least, satisfaction among colleagues and taskoriented leadership style has little or no association towards turnover intention among academicians in higher learning institution.